Properties of Al2O3 thin films deposited on 4H-SiC by reactive ion sputtering. (April 2019) - Fiorenza, P.; Vivona, M.; Di Franco, S.; Smecca, E.; Sanzaro, S.; Alberti, A.; Saggio, M.; Roccaforte, F.
Abstract: In this work, the electrical properties of Al2 O3 films deposited by reactive ion sputtering were investigated by means of morphological, chemical and electrical characterizations. We observe that the electron trapping affecting the insulating layer is mitigated after a rapid thermal annealing (RTA) treatment. The RTA improved also the permittivity (up to 6ε0 ), although the negative fixed charge remains in the order of 10 12 cm −2 . However, the temperature dependent electrical investigation of the metal-oxide-semiconductor (MOS) capacitors demonstrates that the room temperature Fowler-Nordheim electron barrier height of 2.37 eV lies between the values expected for SiO2 /4H-SiC and Al2 O3 /4H-SiC systems.